PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM (Studi Empiris pada Emiten yang Konsisten Masuk dalam Indeks LQ45 Tahun 2015-2017) - Vika Qorinawati; Agustinus Santosa Adiwibowo (Diponegoro Journal of Accounting, 2019)
Abstract Berbahasa Inggris. This study aims to obtain empirical evidence and analyze the effect of financial performance to the share price.The data used as samples in this study are secondary data in the form of annual reports. The population of this study are companies listed on the Indonesia Stock Exchange (IDX) and which consistently enter the LQ45 index for three consecutive years in 2015-2017. This study uses 36 companies using purposive sampling method. Data analysis was carried out by descriptive statistical analysis, classical assumption test and hypothesis testing with multiple linear regression analysis.The results of this study indicate that liquidity (current ratio) has a positive and significant effect, then profitability (return on assets) has a positive and significant effect on stock prices, while activity (total assets turnover) has a positive and insignificant effect on stock prices